Revitalising Traditional Malay Cultural Identity Based on Early Muslim Gravestones in Penang Island - Muhammad Uzair Ismail, (Wacana Seni Journal of Arts Discourse, 2025)
The Batu Nisan Aceh in Penang, particularly that of Tunku Syed Hussain Al-Aidid, has received limited scholarly attention, often overshadowed by colonial narratives centred on Francis Light and the British acquisition of the island. This historiographical gap has contributed to the marginalisation of Malay cultural identity as the original settlers of Penang. It has obscured the region’s broader historical connections to the Dar al-Islam of the Islamic West. This study aims to revitalise and reposition Malay cultural identity by conducting a visual analysis of the decorative repertoire on Tunku’s tombstone, contextualised within Penang’s historical landscape and its ties to Aceh, as well as the Turkic-Islamic dynasties of India and the Eastern Islamic world. The findings indicate that Malay-Islamic art in Penang exhibits clear cultural and aesthetic links to the Turco-Persian artistic tradition, propagated by Islamic dynasties such as the Ottomans, Rasulids, Delhi Sultanate, and the Kingdom of Ormus. This is reflected in specific motifs on Tunku’s tombstone, including the Rub? al-Hizb (?), ciharberk, mihrab images, kit?a, zencirek and salbek, many of which are common in Qur’anic illumination (tezhib). These shared visual elements suggest transregional artistic exchange, possibly initiated during the reign of Ottoman Sultan Suleym?n I the Lawgiver (r. 1520–1566 CE) or earlier. Contrary to earlier claims that Tunku’s tombstone is an “imitation,” the analysis confirms it to be a unique and original design, with its motifs serving as symbolic markers of the deceased’s status, lineage, and spiritual authority. This study underscores the need for further research into Malay heritage in Penang, where symbolism in ornamentation often conveys identity and societal role in the absence of inscribed names, reflecting a cultural preference for modesty, hegemony and reverence.